Shrimp Hemocyte Iridescent Virus (SHIV): An Emerging Shrimp Pathogen - Waikhom, David; Ngasotter, Soibam; Devi, Laishram Soniya (Chronicle of Bioresource Management, 2023)
The target of more production in aquaculture needs the intense intervention of the farming practices with extreme stocking density and other inputs, which ultimately leads to stress in the cultured system. As a result of this, many viral diseases have emerged in the shrimp aquaculture industry. Recently, the shrimp hemocyte iridescent virus (SHIV) that causes disease in shrimps and prawns has emerged as a potential threat to the shrimp aquaculture industry. The mortality rate of the disease caused by the virus is over 80%. SHIV was first reported in China in 2014, leading to significant economic losses to the shrimp farming industry. Thereafter, it has been reported in some shrimp farms in Thailand. Awareness about SHIV among stakeholders in the aquaculture sector is necessary to control and prevent further outbreaks. This article highlights the clinical signs, host species, target tissue and histopathology, geographical distribution, and preventive measures of SHIV infection.